Représentations sociales du stress chez des déplacés climatiques du quartier Nan Orèl, Nord-Ouest d’Haïti - Ammcise Apply; Alice Corbet; Julien Déroy; Lucainson Raymond; Evens Emmanuel (Études Caribéennes, 2022)
This study investigates the relationship between Major Climatic Events (MCE) and Stress among 33 climate displaced people in Nan Orèl, a popular neighbourhood in the North-Western Department of Haiti, to determine their Major Life Stressor (MLS). This population is constantly exposed to flooding due to the extreme climatic conditions of its area of residence facing alteration and anthropic phenomena which intensify the erosion and soil washing processes. The study was conducted using a standard association and evocation questionnaire, inspired by the structural approach of Social Representations, to identify common constructs of stress among the respondents. The results reveal that i) 97% of the population had experienced symptoms similar to post-traumatic stress; ii) 100% of the population said that they had suffered psychosomatic symptoms reflecting the usual stress experienced after natural disasters. Moreover, 67% of the population stated that stress is characterized by intrusive thinking that can lead to sickness and is not related to the ECM. Consequently, for this population (82%), the Major Life Stressor is more likely to be their children’s illness.